(untitled) (Mongolian Journal of Arts and Culture, 2023)
One vital field of choreography is to study top dance creatures reserved into golden fund of Mongolian dances. Within the framework of this research article, we have conducted some observations and analysis on famous choreographer Lamjav’s creatures such as “Morit tsereg” (Cavalry), “Цэнхэр дурдан алчуур” (Blue silk scarf), “Uran khee” (Marvelous ornament) etc. The personal life and work experiences of this choreographer have become a foundation of creation of these art works. A composer Terbish has composed melodies for these three creatures as the wonderful combination of these talented choreographers and music composer has also become the outstanding results of their achievements. Mr. Lamjav used to make models of the dance costumes personally through personal choice of colors and materials for dresses and costumes and used the stage lightening and technique for creation of wonderful stage and dance environment. From his creatures you can see that he could have joined all the tools and methods into a wonderful combination for the expression of dance works. Cavalry and Blue Silk Scarf were a military work expressing the warriors of Khalkh Gol World War period and reflecting the mentality of military officers and warriors of that period through perfect combination of Mongolian national dance movements and tactics with army dance features and typology so that it has become a renovation and update in the Mongolian army dance. Marvelous ornament is a unique creature that expresses various Mongolian ornaments through dance imaginations as a main tool of ornamental expression. Moreover, it has also expressed the love relations of young people in comparison with ornamental figures and composed in perfect combinations as a feature of the creature. Research works on choreographer Lamjav will be vital for its opportunities granted to younger performers, dancers, and choreographers to learn experiments of olden experienced choreographers and to clarify dance creature composition of the 20th century Mongolian traditional dance art. Нэрт бүжиг дэглээч Д.Ламжавын зарим бүтээлд хийсэн ажиглалт Хураангуй: Монголын бүжгийн алтан санд орсон шилдэг бүжгийн бүтээлийг судлан шинжлэх нь бүжиг судлалын нэг чухал чиглэл юм. Тус өгүүллийн хүрээнд нэрт бүжиг дэглээч Д.Ламжавын “Морьт цэрэг”, “Цэнхэр дурдан ал чуур”, “Уран хээ” хэмээх бүжгийн бүтээлд ажиглалт, дүн шинжлэл хийсэн болно . “Морьт цэрэг” бол өвлийн цаснаар морио унаад дархан хилээ манаж яваа хилчин дайчдын дүрээр ХХ зууны монголын түүхэнд морьт цэргүүдийн гүйцэтгэсэн үүрэг, баатарлаг гавьяаг илэрхийлжээ. Бүжгийн хувцас, тайзны гэрэлтүүлэг, техникийн шийдэл нь тус бүжгийн дүр, орчныг бүрэлдүүлэхэд чухал нөлөө үзүүлсэн байна. “Цэнхэр дурдан алчуур” нь цэрэгт мордож буй болон эр цэргийн албаа нэр төртэй хаагаад ирж буй залуус, ар амьдралаа авч яваа саальчин бүсгүйчүүдийн хоорондын харилцааг харуулсан бүтээл юм. Тус бүтээл нь хөдөө нутгийн ахуй амьдралын дэвсгэр дээр эрчүүдийн дүрийн өсөлтийг тод томруун илэрхийлснээрээ онцлогтой . “Уран хээ” бол баяр наадмын го ёлоо өмссөн залуус уулзан учирч, тоглож наадаж, бие биедээ сэтгэлтэй болж, өрх гэр үүсгэж байгааг бүжгийн хэлээр харуулсан бүтээл болно. Тэрхүү өгүүлэмжийг нь монгол хээг бүжгийн зураглалаар бүтээсэн бэлгэдэлт дүрслэл улам тодруулж өгдөг. Дээрх бүжгүүд нь залуу уран бүтээлчдэд жишиг болохуйц бүтээл бөгөөд бүжиг дэглээчийн арга барил, туршлага, эрдэм ухааныг танин мэдэхэд чухал эх хэрэглэгдэхүүн болж байна. Түлхүүр үг: сэдэв, дүр, зохиомж, санаа, хөгжим